Kaedah pembinaan soalan berkualiti - Chik, Abdul Rahman (2016)
It was about procedures for preparing standard question papers. The presentation discussed steps of preparing question papers starting with planning with TOTS, followed by marking schemes and the question papers. For more understanding on the subject, the presentation begun with explanation on Outcome-Based Education (OBE) and its components: Vision, Mission, Program Educational Objectives (PEO), Program Outcomes (PO), and Course Learning Outcomes (CLO). The discussion was mainly on the relationship and connection between, CLO, course content, instructional strategies and assessment. This specialized workshop covered both theory and practice. The random samples presented by English, Arabic and Communication for Dakwah lecturers.